Análise metabolômica dos clones de cajueiro anão (Anacardium occidentale L.): aspectos micromoleculares da tolerância a seca - Martins, Robson Moreira (2021)
The cashew tree (Anacardium occidentale L.) is a tropical plant, native to the coast of northeastern Brazil, dispersed throughout most of its territory. The cashew crop has 98% of the country's production concentrated in the semiarid region, in the states of Ceará, Rio Grande do Norte and Piauí. The main characteristic that marks the region is the rainfall index, which is low and poorly distributed, causing the vegetation to suffer from water scarcity. The Brazilian semiarid region is a unique region, an extreme climate biome, with unique edaphoclimatic, biological, ecological, and social economic conditions. Thus, the development of drought-tolerant cashew cultivars is necessary, which requires a solid knowledge of the metabolomic, and biochemical processes involved with different physiological mechanisms. Studies on micromolecules (secondary and primary metabolites) that can be classified as drought tolerance biomarkers can accelerate the process of genetic improvement. Thus, the present work analyzed the metabolomic profile of drought tolerant and susceptible dwarf cashew clones, using ultra-efficiency liquid chromatography techniques coupled with high resolution mass spectrometry (UPLC-HRMS) and nuclear magnetic resonance (NMR). Chemometric tools were used, such as: principal component analysis (PCA) and combined partial orthogonal analysis (OPLS-DA) and PLS-DA. For the drought tolerant clone six known metabolites were identified as the most important by two different methods, PCA and OPLS-DA. The most pronounced increase in micromolecule accumulation in drought-tolerant clones due to water stress was detected by the UPLC-HRMS technique, identifying the following biomarkers: Catechin, Trigaloyl Glucose, Camperol Hexoside I or Luteolin Hexoside I/Quercetin 3-O-Rhamnoside, Camperol Hexoside II or Luteolin Hexoside II, Quercetin Galoyl Pentoside I, and Amnentoflavone or Agatisflavone. Differentiated NMR analysis showed that tolerant clones expressed a profile of primary metabolites with higher levels of glucose and fructose. Metabolic changes considering drought conditions highlighted the sets of micromolecules identified as tolerance biomarkers, which affect the metabolic and physiological adjustment of dwarf cashew clones, thus ascertaining the impacts of drought. The data generated can be used to discard genotypes that are unfavorable to breeding systems for the development of new adapted clones based on the choice of biomarkers.